Digital Culture as a Moderating Factor in Increasing Digital Literacy - Achmad Tavip Junaedi; Nicholas Renaldo; Indri Yovita; Kristy Veronica; Sudarno Sudarno (First Ciera Publisher, 2023)
This research aims to develop a measurement of digital culture as a moderating factor in increasing digital literacy. By using an interdisciplinary approach that combines the concepts of digital literacy and digital culture, this research contributes to the understanding of how digital culture can influence the effectiveness of digital literacy programs. Literary studies provide a theoretical foundation for identifying key dimensions of digital literacy and digital culture. Based on literature findings, a measurement instrument was developed and validated to measure digital cultural norms, values, and practices that moderate digital literacy. Data was collected through surveys from a sample of respondents covering a variety of cultural backgrounds. Data analysis using statistical methods reveals that digital culture has a significant impact in moderating the relationship between digital literacy and other variables that influence technology mastery. The conclusion of this research emphasizes the importance of considering digital culture in digital literacy development programs. Methodological limitations and suggestions for future research are also identified. This research paves the way for a deeper understanding of the complexity of the relationship between digital literacy and digital culture, with practical applications for developing more effective digital literacy strategies in an increasingly technologically connected society.